Inhibition of nucleophosmin 1 suppresses colorectal cancer tumor growth of patient -derived xenografts via activation of p53 and inhibition of AKT. Issue 2 (1st February 2021) - Yu, Angel C.Y.; Chern, Yi-Jye; Zhang, Peter; Pasiliao, Clarissa C.; Rahman, Mahbuba; Chang, George; Ren, Jianhua; Tai, Isabella T.
ABSTRACT: The nucleophosmin 1 (NPM1) protein is frequently overexpressed in various cancers compared to normal tissues and represents a potential biomarker for maliganancy. However, its role in colorectal cancer (CRC) is still not fully understood. In this report, we show that NPM1 levels in CRC correlate with prognosis and sensitivity to chemotherapy. NPM1 expression was found to be significantly increased in CRC tumors ( P < .001) and was associated with poor overall 5-year survival ( P < .05). For individuals with Stage IV disease, this represented a reduction in survival by 11 months ( P < .01; HR = 0.38, CI [0.21, 0.69]. In vitro, we show that NPM1 gene silencing enhanced the chemosensitivity of CRC cells and that pharmacological inhibition of NPM1 by NSC348884 triggered the onset of programmed cell death. Our immunofluorescence microscopy and immunoblot analyses also revealed that blocking NPM1 function sensitized CRC cells to chemotherapy-induced apoptosis through a mechanism that involves proteins in the AKT pathway. Consistent with the in vitro data, our patient-derived CRC xenograft model showed that inhibition of NPM1 suppressed tumor growth and attenuated AKT signaling in vivo . Moreover, LY294002, an inhibitor of the PI3K/AKT pathway, restored the chemosensitivity of CRC cells expressing high levels of NPM1. The findings that NPM1's expression in CRC tissue correlates with prognosis and supports anti-apoptotic activity mediated by AKT signaling, further our understanding of the role of NPM1 in CRC.